1990
DOI: 10.1177/097133369000200203
|View full text |Cite
|
Sign up to set email alerts
|

Examination Stress and Test Anxiety: A Cross-Cultural Perspective

Abstract: This is a comparative study of the examination stress assessed either as test anxiety or in terms of its worry and emotionality components in 7,679 high school students (males and females) from four Asian (Indian, Jordanian, Chinese and Korean) and five Euro-American (Hungarian, Turkish, Indian, German and American) cultures. These comparisons have been made on the basis of data reported in the studies which used the English Test Anxiety Inventory (Spielberger, 1980), or its psychometrically equivalent version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
2
11
1
Order By: Relevance
“…Thus, this finding does not support Hypothesis 5. Interestingly, this conclusion is contrary to the existing literature since it is discovered that female students have a higher level of test anxiety than male students irrespective of the level of study and cultural background (Van der Ploeg and Hulshof, 1984;Sharma and Sud, 1990;Kleijn, van der Ploeg and Topman, 1994;Karimi and Venkatesan, 2009). Finally, in the context of nationality backgrounds, the local Malaysian students have a higher level of test anxiety in mathematics than their peers from overseas.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Thus, this finding does not support Hypothesis 5. Interestingly, this conclusion is contrary to the existing literature since it is discovered that female students have a higher level of test anxiety than male students irrespective of the level of study and cultural background (Van der Ploeg and Hulshof, 1984;Sharma and Sud, 1990;Kleijn, van der Ploeg and Topman, 1994;Karimi and Venkatesan, 2009). Finally, in the context of nationality backgrounds, the local Malaysian students have a higher level of test anxiety in mathematics than their peers from overseas.…”
Section: Resultscontrasting
confidence: 72%
“…It has been found that female students experience higher levels of test anxiety than males irrespective of cultural background (Van der Ploeg and Hulshof, 1984;Sharma and Sud, 1990;Kleijn, van der Ploeg and Topman, 1994;Karimi and Venkatesan, 2009). However, in this study, an examination goes further whether there is a significant difference in AP between the gender groups when dealing with test anxiety.…”
Section: Hypothesis 3 There Is a Significantly Positive Correlation Bmentioning
confidence: 55%
“…Cultural differences in anxiety have been observed in cognitive, affective, and behavioural components (Zeidner, 1998). Sharma and Sud (1990), for example, conducted a comparative study of TA through using a sample of 7,679 high school students from four Asian and five EuroAmerican countries. While TA was found to be universal, differences in the intensity and pattern of TA were found both between and within the different cultural groups.…”
Section: Cultural Variants and The Tai-gmentioning
confidence: 99%
“…The findings from the present study are the first to be reported on the psychometric properties of the TAM-C scores with a sample of college students outside of the United States. Mowbray and colleagues (2015) have stated that measures used to assess test anxiety must show validity in the country where individuals plan to use them, as the pattern and level of test anxiety may differ in different countries (Bodas & Ollendick, 2005; Sharma & Sud, 1990). Even though there are many cultural similarities between Canada and the United States, there are also many differences between the two countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Canada has a larger proportion of its minorities attending Canadian universities than U.S. minorities attending U.S. universities (Bowman, 2000). Bodas and Ollendick (2005) indicated that the psychosocial cultural context must be considered when conducting research in the area of test anxiety, as the pattern and level of test anxiety may differ (Bodas & Ollendick, 2005;Sharma & Sud, 1990). This suggests that measures used to assess test anxiety must show validity in the country where researchers and clinicians plan to use them (Mowbray, Jacobs, & Boyle, 2015).…”
Section: Test Anxiety and The Canadian And Us Cultural Contextsmentioning
confidence: 99%